Ecology and biotechnology of the genus Shewanella - Hau, Heidi H; Gralnick, Jeffrey A (Annual review of microbiology, 2007)
The shewanellae are aquatic microorganisms with worldwide distribution. Their hallmark features include unparalleled respiratory diversity and the capacity to thrive at low temperatures. As a genus the shewanellae are physiologically diverse, and this review provides an overview of the varied roles they serve in the environment and describes what is known about how they might survive in such extreme and harsh environments. In light of their fascinating physiology, these organisms have several biotechnological uses, from bioremediation of chlorinated compounds, radionuclides, and other environmental pollutants to energy-generating biocatalysis. The ecology and biotechnology of these organisms are intertwined, with genomics playing a key role in our understanding of their physiology.